Identification and functional prediction of lncRNAs associated with intramuscular lipid deposition in Guangling donkeys - Peng, Yongdong; Zhu, Mingzhu; Gong, Yunyi; Wang, Changfa (Frontiers in Veterinary Science, 2024)
More and more studies have shown that long non-coding RNAs (lncRNAs) play key regulatory roles in various biological processes. However, the importance and molecular regulatory mechanisms of lncRNAs in donkey intramuscular fat deposition remain to be further investigated. In this study, we used published transcriptomic data from the longissimus dorsi muscle of Guangling donkeys to identify lncRNAs, and obtained 196 novel lncRNAs. Compared with the coding genes, the novel lncRNAs and the known lncRNAs exhibited some typical features, such as shorter transcript length and smaller number of exons. 272 coding genes and 52 lncRNAs were differentially expressed between the longissimus dorsi muscles of the low-fat and high-fat groups. The differentially expressed genes were found to be involved in various biological processes related to lipid metabolism. The potential target genes of differentially expressed lncRNAs were predicted by cis and trans. Functional analysis of lncRNA targets showed that some lncRNAs may act on potential target genes involved in lipid metabolism processes and regulate lipid deposition in the longissimus dorsi muscle. This study provides valuable information for further investigation of the molecular mechanisms of lipid deposition traits in donkeys, which may improve meat traits and facilitate the selection process of donkeys in future breeding.